Kajian mutu bahan baku rumput laut (Eucheuma SP.) dan teknologi pangan olahannya - Rizal Alamsyah; Nami Lestari; Reno Fitri Hasrini (Jurnal Dinamika Penelitian Industri, 2013)
Seaweed is one of the strategic commodities in fisheries revitalization program in Indonesia. The problems faced by seaweed producers are the low quality and products diversification of seaweeds due to traditional post-harvest handling and unknown critical factors as quality benchmark of seaweeds products. This study was aimed to determine the condition of the quality of raw materials and end products that have been produced on the market and give recommendations for better seaweed processing technology. The steps taken were the collection of data and information, purchase of raw materials and seaweed based food products, analysis of various seaweed products purchased from the survei areas, process improvement based on the results of analysis, and product analysis as the results of process improvement results. Raw material quality of seaweed of Echeuma cottoni in the market are generally not eligible to be qualified as Dried Seaweed (SNI 2690 2:2009) which has the moisture content above 30%, the value of anhydrous weed below 30%, the level of foreign objects above 5% and microbial contamination was sufficiently high (max 1.0 X102 TPC colonies / gram and E.coli maxKeywords : Eucheuma sp, seaweed sweets, seaweed jam, seaweed sweet cake , seaweed crackers, seaweed cheese stickAbstrakRumput laut merupakan salah satu komoditas strategis dalam program revitalisasi perikanan di Indonesia. Permasalahan yang dihadapi adalah rendahnya mutu rumput laut dikarenakan masih tradisionalnya penanganan pascapanen serta tidak diketahuinya kritikal faktor yang dijadikan tolak ukur mutu produk rumput laut. Penelitian ini ditujukan untuk mengetahui kondisi mutu bahan baku dan produk jadinya yang telah diproduksi yang beredar di pasaran, serta memberikan rekomendasi teknologi pengolahan rumput laut yang lebih baik. Tahapan yang dilakukan adalah pengumpulan data dan informasi, pembelian bahan baku dan produk pangan berbasis rumput laut, analisis berbagai produk rumput laut yang dibeli dari daerah survei, perbaikan proses berdasarkan hasil analisis, dan analisis produk hasil perbaikan proses. Mutu bahan baku rumput laut jenis Echeuma cottoni di pasaran umumnya belum memenuhi syarat Rumput Laut Kering (SNI 2690 2:2009) yaitu kadar air masih diatas 30%, nilai anhydrous weed dibawah 30%, kadar benda asing di atas 5% dan cemaran mikrobanya cukup tinggi (ALT maks 1,0x102 koloni/gram dan E.coli maksKata kunci : Eucheuma sp, manisan basah rumput laut, selai rumput laut, dodol rumput laut, kerupuk rumput laut, kertas keju rumput laut